(untitled) - Gordon, Robert J. (Cambridge, UK, 2003)
Seventeen essays include three previously unpublished works and offer sharply etched views on the principal topics of macroeconomics: growth, inflation, and unemployment. Robert Gordon re-examines their salient points in a new accessible introduction to modern macroeconomics. Each of the four parts into which the essays are grouped also offers a new introduction. The foreword by Nobel Laureate Robert M. Solow comments on the continuing importance of these essays which date from 1968 to the present.
Keywords: Macroeconomics,Employment ( economic theory ),Industrial productivity,Economic policy; United states